Konsep Filsafat Hukum Menurut Jeremy Bentham - Songbes, Leo (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2023)
Introduction: If you know Jeremy Bentham in his moral teachings on utilitarianism, it is often said there that the principle of utility he discovered is also used in constructing the concept of law. Purposes of the Research: This research aims to find out how the principle of utility becomes the basis for establishing a legal system. Methods of the Research: The methods used in this study is a qualitative method with a descriptive and interpretive analysis approach. Results Originality of the Research: The research results show that the usability test on legal institutions and practices makes the principle of utility a critical instrument for assessing the performance of a legal institution. For Bentham, law is an order from a sovereign power or imperative law. The law must have substance and legal form. Legal substances are certain legitimate (sovereign) legal institutions within the state that are authorized to make and promulgate laws, and that law must be written in law. The legal form in question is codification.